DETERMINANTS OF ARTISAN PRODUCTIVITY ON CONSTRUCTION SITES IN ADAMAWA STATE, NIGERIA: THE ROLE OF INCENTIVES - Anum, Iorwuese; Yakubu, Yohanna; soji, Solomon M.; Isa, Felix N. (FUDMA Journal of Sciences, 2026)
This study examined the nexus between incentives and artisan productivity on selected building construction sites in Adamawa State, Nigeria. An exploratory survey design was adopted, with data collected from 96 artisans including masons, carpenters, plumbers, iron benders and tilers out of a population of 130 artisans using purposive sampling. Representing a 73.8% response rate. A structured questionnaire with Likert-scale items was used to collect data. The reliability of the instrument was confirmed with Cronbach’s Alpha values above 0.70. The data collected were analyzed using descriptive and inferential statistics in SPSS version 25. Findings showed that financial incentives dominate the industry, with performance bonus ranking highest (0.87), followed by profit sharing (0.85), gain sharing (0.80), and discretionary bonuses (0.79), while non-financial incentives ranked lowest (0.51). Correlation results indicated strong positive relationships between incentives and productivity components: labour (r = 0.73), capital (r = 0.75), materials (r = 0.69), and management and technology (r = 0.72), all statistically significant (p < 0.05). Regression analysis revealed that incentives significantly predict productivity, explaining 51% of its variation (R² = 0.51, p = 0.000), while combined incentives account for 45.5% (R² = 0.455). The study concludes that a balanced mix of financial and non-financial incentives enhances artisan productivity.
Keywords: Artisans,; Building,; Construction,; Incentive,; Productivity